Process Design of Cooperative Education Management System by Cloud-based Blockchain E-portfolio - Wanotayapitak, Sukosol; Saraubon, Kobkiat; Nilsook, Prachyanun (International Journal of Online and Biomedical Engineering (iJOE), 2019)
The digital competence is necessary for 21st century living, but from several countries survey, a large number of people still have insufficient digital competence. Moreover, from literature study found three problems of today cooperative education information system, (1) lack of information sharing among university community, (2) lack of connect information to public, and (3) lack of enhancing 21st century learning skill. This paper proposes a process design of cooperative education management system by using the integration of cooperative education, E-Portfolio, digital competence framework 2.0, cloud computing technology, and blockchain technology. These processes make result of digital competence assessment credible and share to open digital labor market finally.